PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BIOLOGI BERBASIS GAMBAR PADA MATERI POKOK PLANTAE UNTUK SMA - Novita, Vivy Rizki; Ardi, Ardi; Risdawati, Renny (STKIP PGRI Sumbar, 2013)
ABSTRACT Worksheet students is learning materials that are commonly used in the learning process. On Plantae material, discussed various characteristics of plants and it required students worksheet based on the image. This study aims to determine the validity and practicality of students worksheet based on image that had been developed . This study used3 of 4-D developing model (define, design, develop). Results of this study indicated that students worksheet based on the image have validity value 94.25% (categories: very valid) and the teachers practicalities value is 97.80% (categories: very practical) as well as the students practicalities value is 93.6% (categories: very practical).